Pelatihan dan Penguatan Komunikasi Kepada Kelompok Tani Tentang Pembibitan Sawit Bersertifikasi - Rosliana Lubis; Effiati Juliana Hasibuan; Ahmad Prayudi; Affandi Affandi (I-Com: Indonesian Community Journal, 2024)
This community service activity aims to provide training and strengthen communication to farmer groups about certified oil palm nurseries. The activity partner is a farmer group (Poktan) Putra Mandiri of Gunung Ambat village, Sei Bingai District, Langkat Regency, North Sumatra. The productivity of oil palm fresh fruit bunches (FFB) in this village is still low because the oil palm seeds used are "mariles ” seeds or random seeds that are not certified. The form of activities carried out are: (a) Training to partners on certified oil palm seedlings and seedling techniques, and (b) Practical practice of planting certified oil palm sprouts on partner land with DXP Simalungun variety. The results of the training and practical practice showed an increase in the knowledge and skills of farmer groups about certified palm oil seeds and nursery techniques, as well as the formation of a more effective communication model in the form of a combination of theory and practical practice. Strengthening this communication is key in conveying clear and applicable information, so that it can encourage the sustainability of more productive oil palm farming businesses.